P87 Benchmarking of paediatric difficult asthma physiotherapy services. (15th November 2017) - Wells, C; Collins, N; Bush, A; Flemming, L; Saglani, S
Abstract : Introduction: Children with difficult asthma (DA) comprise 2%–5% of all children with asthma but use 50% of national asthma health care provisions, they have high levels of morbidity and poor quality of life. Guidelines recommend children with DA should be assessed by a specialist multidisciplinary team, including physiotherapy, to confirm an asthma diagnosis, exclude alternative causes of persistent symptoms, manage co-morbidities, confirm adherence and ensure treatment is appropriate. Physiotherapy may involve breathing pattern retraining, airway clearance, exercise, symptom differentiation, relaxation techniques, self-management and overcoming barriers to adherence. Currently there are no validated condition specific screening tools, outcome measures, methods of assessment or standardised treatments for breathing pattern disorders in children. Physiotherapy intervention improves asthma symptom scores, quality of life 1 and A and E attendances and hospital admissions. 2 We aimed to investigate physiotherapy services and treatments currently being offered at paediatric centres nationally and whether the current guideline recommendations were being met. Method: Physiotherapists from twenty-two UK hospitals were invited to complete a questionnaire about service size and provision, referral systems, screening tools, assessment and outcome methods and treatments offered. Results: 18/22 centres responded. Sixteen (89%) did not have funded DA physiotherapy, twelve (66%) had no dedicated DA physiotherapy time. Seventeen (94%) relied on referrals from DA consultants and nurses, rather than physiotherapists having the opportunity to routinely assess DA patients. There was no consensus about paediatric screening tools, assessment protocols or outcome measures (figure 1 ). There was marked variation in what was offered ranging from only performing airway clearance reviews to a full breathing pattern assessment, cough management, sleep, continence, exercise prescription, musculo-skeletal treatment, relaxation/anxiety management, sinus management and advice and education. Conclusion: Paediatric physiotherapy services for DA are largely ad hoc and reactive. Despite guideline recommendations, physiotherapy for paediatric DA is currently an unmet clinical need with no agreed diagnostic or management algorithms. There is a clear need to better define the role of physiotherapy in DA. References: Barker NJ. ERJ Open Res 2016, Sep 26;2(3).pii. 00103–2015. Lilley A. Arch Dis Child2016, Sept;101(9):e2.